Canine Models of Inherited Musculoskeletal and Neurodegenerative Diseases - Story, Brett D.; Miller, Matthew E.; Bradbury, Allison M.; Million, Emily D.; Duan, Dongsheng; Taghian, Toloo; Faissler, Dominik; Fernau, Deborah; Beecy, Sidney J.; Gray-Edwards, Heather L. (Frontiers in Veterinary Science, 2020)
Mouse models of human disease remain the bread and butter of modern biology and therapeutic discovery. Nonetheless, more often than not mouse models do not reproduce the pathophysiology of the human conditions they are designed to mimic. Naturally occurring large animal models have predominantly been found in companion animals or livestock because of their emotional or economic value to modern society and, unlike mice, often recapitulate the human disease state. In particular, numerous models have been discovered in dogs and have a fundamental role in bridging proof of concept studies in mice to human clinical trials. The present article is a review that highlights current canine models of human diseases including Alzheimer’s disease, degenerative myelopathy, neuronal ceroid lipofuscinosis, globoid cell leukodystrophy, Duchenne muscular dystrophy, mucopolysaccharidosis, and fucosidosis. The goal of the review is to discuss canine and human neurodegenerative pathophysiologic similarities, introduce the animal models, and shed light on the ability of canine models to facilitate current and future treatment trials.